Personalized Medicine in Screening for Malignant Disease: A Review of Methods and Applications. Issue 8 (January 2013) - Schmalfuss, F.; Kolominsky-Rabas, P.L.
Personalized medicine (PM) is currently a hot topic in the professional world. It is often called the medicine of the future and has already achieved resounding success in the area of targeted therapy. Nevertheless, integration of the concepts of PM into routine clinical practice is slow. This review is intended to give an overview of current and potential applications of PM in oncology. PM could soon play a decisive role, especially in screening. The relevance of PM in screening was examined in the case of four common cancers (colorectal cancer, lung cancer, breast cancer, and prostate cancer). A literature search was performed. This showed that biomarkers in particular play a crucial role in screening. In summary, it can be emphasized that there are already numerous known promising biomarkers in malignant disease. This results in several possibilities for individualizing and revolutionizing screening.